Scarcity Effect, FOMO, WOM, and Influencers in Iftar Snacks: A Study of Marketing Strategies During Ramadan in Indonesia - Sora Baltasar; Dani W Wibowo; Phintoko Akhbar Akriyono; Ana Rohana; Sandi Yuda Wardani; Dini Puspitasari (International Journal of Islamic Business and Management Review, 2025)
This study examines the sale of takjil (iftar snacks) by Micro, Small, and Medium Enterprises (MSMEs) during Ramadan in Indonesia, emphasizing the integration of social, cultural, and religious values in business practices. Using a narrative review method, this research analyzes relevant literature to explore iftar snacks consumption patterns and marketing strategies adopted by MSMEs. Findings indicate that Ramadan is not only a spiritual occasion but also a time of increased social cohesion and economic opportunity. The tradition of iftar snacks stalls, embraced by both Muslims and non-Muslims, reflects local wisdom and a spirit of togetherness. Marketing strategies based on Fear of Missing Out (FOMO), scarcity, and word of mouth have proven effective, particularly through digital platforms. However, many MSMEs still struggle to understand consumer behavior and manage excess inventory. The study concludes that MSME success during Ramadan depends on their ability to present products attractively, build emotional connections with consumers, and implement marketing strategies that are responsive to cultural and social values.